Revolutionizing Recruitment: Navigating Recruitment Trends for Long-Term Success - Santhanam, Uthaya Prakash (2023)
Recruitment plays an essential role in organizational success by ensuring the acquisition of competent and qualified individuals to meet the ever-changing business demands. The case study highlights recruitment best practices and trends, key findings and implications on employers, employees and job seekers. This starts with the effective recruitment strategies vitality in attracting, selecting and hiring top talent and enhancing organizational performance and employer branding. It further explores various recruitment methods, including traditional approaches such as job postings and employee referrals and modern techniques such as Glassdoor reviews and online platforms, social media, and artificial intelligence-driven tools. Discussion on the impact of technology on recruitment process, emphasizing the growing use of applicant tracking systems (ATS), automated screening tools and recruitment related methodology are included. It explores and weighs the challenges and benefits associated with these advancements, covering enhanced efficiency, bias-free, diversity and inclusiveness approach and potential ethical concerns in the recruitment space. Furthermore, the case study digs into the importance of employer branding and its role and influence in attracting and retaining both new and existing employees and the significance of a positive employer brand image, effective communication of organizational values, and online reviews, newsfeed and posts in shaping candidate perceptions. Additionally, it discusses the rising popularity global changes and its impact on recruitment at large. In summary, this research provides a comprehensive overview of recent best practices, the evolution in recruitment, highlighting the importance of effective strategies, the influence of technology and employer branding plus the evolving expectations of job seekers. The best practices and recommendations are important in adopting innovative approaches to attract and retain top talent in today's dynamic employment landscape.